2012
DOI: 10.1111/ijsw.12000
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and psychological distress among young adults in the Nordic countries: A review of the literature

Abstract: Reneflot A, Evensen M. Unemployment and psychological distress among young adults in the Nordic countries: A review of the literature This article reviews Nordic research, published from 1995 and onwards, on the relationship between unemployment and mental health among young adults. Cross-sectional, longitudinal and time-series studies are included. Cross-sectional studies show that the unemployed experience more mental health problems than the non-unemployed. Leaving unemployment is associated with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
85
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 35 publications
10
85
0
2
Order By: Relevance
“…We also found that, for both men and women, a poor financial situation was related to a higher likelihood of a possible mental disorder. This finding is supported by the literature, which found positive associations between mental health and a comfortable financial situation in youth [33, 34, 54]. We also found that living with a partner is consistently related to both adverse mental health outcomes for men, which is consistent with the literature as well [36].…”
Section: Discussion and Limitationssupporting
confidence: 92%
“…We also found that, for both men and women, a poor financial situation was related to a higher likelihood of a possible mental disorder. This finding is supported by the literature, which found positive associations between mental health and a comfortable financial situation in youth [33, 34, 54]. We also found that living with a partner is consistently related to both adverse mental health outcomes for men, which is consistent with the literature as well [36].…”
Section: Discussion and Limitationssupporting
confidence: 92%
“…Yet gendered norms have changed, as evidenced by the increased rate of labor force participation by women (Fortin 2015) and much more modest gender differences in attachment to jobs than once presumed (Sweet et al 2016). Relevant empirical findings are also mixed and inconclusive—the impacts of unemployment on mental health were stronger for men in some studies (Brydsten et al 2015; Paul and Moser 2009) but for women in others (Hammarström et al 2011; Reneflot and Evensen 2014). Other studies reported no gender differences (Frasquilho et al 2016; Nieuwenhuis et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such adverse mental health impacts can be more concentrated among young adults. First, young adults, also referred to as transitional age youth (Burt and Paysnick 2012), are more likely to lose their jobs compared to older adults (McGee and Thompson 2015; Reneflot and Evensen 2014). In January 2017, for example, the unemployment rate among young adults was almost double the national average (8.0% vs. 4.3%).…”
Section: Introductionmentioning
confidence: 99%
“…3 4 6 An extensive body of literature suggests that youth unemployment is related to a decrease in physical and mental health and an increase in smoking and alcohol consumption. [7][8][9][10][11][12][13][14][15][16] Further, youth appears to be a sensitive time period in life, as recent studies have found that the effect of youth unemployment on mental health remains in adulthood, independent of later unemployment experiences. 6 14-16 The relationship between unemployment and ill health is, however, more complex as the effect could differ depending on the national rate of unemployment.…”
Section: Introductionmentioning
confidence: 99%
“…21 Previous research on youth unemployment has to a great extent relied on self-reported measures to assess the health or health behaviours. 13 19 24 Thus, there is a need to include more severe health outcomes, such as hospital diagnoses to more comprehensively address the effects of youth unemployment on health later in life. 13 The aims of the current study are (1) to investigate the effect of youth unemployment on mental health during periods of high and low unemployment rates and (2) to explore whether there is any interaction in mental health between labour force status and level of unemployment.…”
Section: Introductionmentioning
confidence: 99%